CONFINEMENT EFFECTS AND ENERGY BALANCE ANALYSES FOR BUCKLING FAILURE UNDER ECCENTRIC LOADING CONDITIONS - Kazakidis V.N. (My University, 2002)
An eccentric loading approach was applied to quantify confinement effects and examine the energy balance in a slab under buckling load. It was indicated that confining pressure provided by fill or broken rock material can prove adequate to control buckling failure under certain loading conditions. The stored strain energy in a slab under eccentric loading conditions, in the vicinity of underground openings was determined to be in the order of 1 MJ.